A case report on pseudohypoaldosteronism with a pathogenic mutation of CA12 causes autosomal recessive isolated hyperchlorhidrosis disorder - Yousef A. Alanazi (Journal of Family Medicine and Primary Care)
Pseudohypoaldosteronism (PHA) is a rare genetic condition characterized by the body’s inability to respond properly to the hormone aldosterone, which is essential for regulating sodium and potassium levels, as well as maintaining blood pressure. The aim is to present this case study on the mutation spectrum of the CA12 gene to help clinicians better recognize autosomal recessive isolated hyperchlorhidrosis disorder caused by CA12 gene mutations. An eight-month-old Jordanian boy presented with vomiting and diarrhea, initially treated for gastroenteritis with IV fluids and oral rehydration. Laboratory results revealed significant electrolyte imbalances, leading to a provisional diagnosis of pseudohypoaldosteronism. Genetic analysis later identified two heterozygous variants in the CA12 gene (c. 585C>A, p.(Tyr195Ter) and c. 635C>T, p.(Pro212Leu)), suggesting a link to autosomal recessive isolated hyperchlorhidrosis disorder. The patient was managed with NaCl supplements, showing improved and stable laboratory results over time. It is concluded that comprehensive genetic analysis is crucial in accurately diagnosing and managing complex electrolyte disorders. The discovery of CA12 gene mutations in this patient shifted the diagnosis from pseudohypoaldosteronism to autosomal recessive Isolated hyperchlorhidrosis disorder. This finding enabled targeted treatment with NaCl supplements, resulting in significant clinical and laboratory improvements.